Penetrating laryngotracheal injuries. Case Report - González, Laura Díez (2008)
Deep laryngotracheal trauma are uncommon lesions that request a fast treatment to keep the airway open. We present a clinical report from a patient with a cervical impact of a metal foreign body, showing an emphysema of the cervical subcutaneous adipose tissue without dysphonia or respiratory symptoms. The airway was kept by a tracheostomy followed by a regional reconstruction of the neck. The outcome is satisfactory comparing our result with other authors.